Math Series #2

Algebra Level 3

If x + 1 x = 3 , x + \frac {1}{x} = 3, find the value of x 4 + x 3 + 1 x 4 + 1 x 3 x^4 + x^3 + \frac {1}{x^4} + \frac {1}{x^3} .


The answer is 65.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sathvik Acharya
Mar 5, 2021

For any number n n , let S n = x n + 1 x n {S_n}=x^n+\dfrac{1}{x^n} . So, we have, S 1 = 3 S 2 = ( x + 1 x ) 2 2 x 1 x = S 1 2 2 = 7 S 3 = ( x + 1 x ) 3 3 x 1 x ( x + 1 x ) = S 1 3 3 S 1 = 18 S 4 = ( x 2 + 1 x 2 ) 2 2 x 2 1 x 2 = S 2 2 2 = 47 x 4 + x 3 + 1 x 4 + 1 x 3 = ( x 4 + 1 x 4 ) + ( x 3 + 1 x 3 ) = S 4 + S 3 = 47 + 18 = 65 \begin{aligned} S_1&=3 \\ \\ S_2&=\left(x+\frac{1}{x}\right)^2-2\cdot x\cdot \frac{1}{x} \\ &=S_1^2-2 \\ &=7 \\ \\ S_3&=\left(x+\frac{1}{x}\right)^3-3\cdot x\cdot \frac{1}{x}\cdot \left(x+ \frac{1}{x} \right) \\ &=S_1^3-3S_1 \\ &=18 \\ \\ S_4&=\left(x^2+\frac{1}{x^2}\right)^2-2\cdot x^2\cdot \frac{1}{x^2} \\ &=S_2^2-2 \\ &=47 \\ \\ x^4+x^3+\frac{1}{x^4}+\frac{1}{x^3}&=\left(x^4+\frac{1}{x^4}\right)+\left(x^3+\frac{1}{x^3}\right) \\ &=S_4+S_3 \\ &=47+18 \\ &=\boxed{65} \end{aligned}

Can you change 85 into 65? Thanks!

Avner Lim - 3 months, 1 week ago

Log in to reply

I have corrected it. Thank you!

Sathvik Acharya - 3 months, 1 week ago

Log in to reply

You're welcome! It is also a very nice explanation.

Avner Lim - 3 months, 1 week ago
Avner Lim
Mar 5, 2021

( x + 1 x ) 2 = x 2 + 1 x 2 + ( 2 × x × 1 x ) = x 2 + 1 x 2 + 2 = 3 2 = 9 x 2 + 1 x 2 = 9 2 = 7 ( x 2 + 1 x 2 ) 2 = x 4 + 1 x 4 + ( 2 × x 2 + 1 x 2 ) = x 4 + 1 x 4 + 2 = 7 2 = 49 x 4 + 1 x 4 = 49 2 = 47 ( x 2 + 1 x 2 ) × ( x + 1 x ) = x 3 + 1 x 3 + x + 1 x = x 3 + 1 x 3 + 3 = 7 × 3 = 21 x 3 + 1 x 3 = 21 3 = 18 x 4 + x 3 + 1 x 4 + 1 x 3 = 47 + 18 = 65 (x + \frac {1}{x})^2 = x^2 + \frac {1}{x^2} +(2 \times x \times \frac {1}{x}) = x^2 + \frac {1}{x^2} + 2 = 3^2 = 9 \rightarrow x^2 + \frac {1}{x^2} = 9 - 2 = 7 \rightarrow (x^2 + \frac {1}{x^2})^2 = x^4 + \frac {1}{x^4} + (2 \times x^2 + \frac {1}{x^2})= x^4 + \frac {1}{x^4} + 2 = 7^2 = 49 \rightarrow x^4 + \frac {1}{x^4} = 49 - 2 = 47 \rightarrow (x^2 + \frac {1}{x^2}) \times (x + \frac {1}{x}) = x^3 + \frac {1}{x^3} + x + \frac {1}{x} = x^3 + \frac {1}{x^3} + 3 = 7 \times 3 = 21 \rightarrow x^3 + \frac {1}{x^3} = 21 - 3 = 18 \rightarrow x^4 + x^3 + \frac {1}{x^4} + \frac {1}{x^3} = 47 + 18 = \boxed{65}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...